Screening Patterns of Nonalcoholic Fatty Liver Disease in Children with Obesity in Canadian Primary Care: A Cross-Sectional Study - Rachael Morkem; Rebecca Theal; David Barber; Jennifer Flemming; John Queenan; Mohit Kehar (Canadian Journal of Gastroenterology and Hepatology)
Background. Nonalcoholic fatty liver disease (NAFLD) is the most common pediatric chronic liver disease, and children with a body mass index (BMI) ≥95th percentile are recommended to be screened for NAFLD by liver enzymes. Objectives. This study aimed to determine the frequency and predictors of screening for NAFLD among children with obesity in Canada and to evaluate a sample of children with suspected NAFLD. Methods. This cross-sectional study used data from the Canadian Primary Care Sentinel Surveillance Network, a repository of electronic medical record data from Canadian primary care practices. Results. Of n = 110,827 children aged 9–18 years, 13.9% (n = 9,888) had a BMI ≥95th percentile. Only 8.7% (n = 859) of these patients were screened for NAFLD in the last year, and 23.6% (n = 2336) were ever screened. Using logistic regression, screening in the last year was associated with demographic and clinical characteristics, including previous liver enzyme assessment, prior antidiabetic prescription, and prior anxiolytic prescription. Among children with suspected NAFLD (n = 1,046), 34.7% had a BMI ≥99th percentile and approximately 8% were at increased risk of significant liver disease. Conclusion. The study revealed low screening rates for NAFLD in Canadian primary care and highlighted the important role of primary care providers in identifying and managing pediatric NAFLD.